A comparative study of socio‐demographic and substance use correlates in early‐onset psychosis. Issue 3 (1st April 2016) - Paruk, Saeeda; Jhazbhay, Khatija; Singh, Keshika; Sartorius, Benn; Burns, Jonathan K
Abstract: Background: Comorbid substance use, particularly cannabis among adolescents with mental illness, is a major public health concern in developing countries with limited mental health resources. Better understanding of the association between cannabis use and other polysubstance use and early mental illness will provide for more targeted early interventions. Aim: This aim of this study was to examine the socio‐demographic profile and cannabis use characteristics among adolescents with first‐episode early‐onset psychosis (EOP) and compare with age‐matched and gender‐matched adolescents with first‐episode non‐psychotic mental illness (controls). Method: Forty‐five adolescents with first‐episode EOP and 45 controls were assessed using a clinical interview, Positive and Negative Syndrome Scale and World Health Organization Alcohol, Smoking and Substance Involvement Screening test (ASSIST) for substance‐related problems. Results: There were significant socio‐demographic differences among the adolescents with EOP (73% Black, 64% from low family income, 44% from rural areas) compared with controls (24% Black, 53% from low family income, 2% from rural areas). Although there was no difference in lifetime cannabis use, EOP adolescents differed in motivation for cannabis use, had increased current cannabis use (38%, P = 0.01) and more frequent use (52%, P = 0.04) compared with controls (16% current and 18% frequent use). EOP adolescents reported more hazardous use with higher ASSIST mean cannabis‐specific involvement scores (EOP 10, 2; controls 2, 3; P = 0.004). Conclusion: The differences in socio‐demographic variables may reflect the marked disparity in access to mental health care for rural Black youth. Psychotic youth may be more vulnerable to comorbid cannabis‐related problems than other mentally ill adolescents. The study highlights the need for early introduction of substance use interventions among adolescents with mental illness.